Fertility preservation in female cancer patients: a single center experience. Issue 1 (16th June 2015) - Sigismondi, Cristina; Papaleo, Enrico; Viganò, Paola; Vailati, Simona; Candiani, Massimo; Ottolina, Jessica; Di Mattei, Valentina E.; Mangili, Giorgia
Abstract: Advances in cancer treatment allow women to be cured and live longer. However, the necessary chemotherapy and radiotherapy regimens have a negative impact on future fertility. Oncofertility has emerged as a new interdisciplinary field to address the issue of gonadotoxicity associated with cancer treatment and to facilitate fertility preservation, including oocyte and ovarian tissue cryopreservation. These fertility issues are often inadequately addressed, and referral rates to oncofertility centers are low. The aim of this study was to report the 3‐year experience of the San Raffaele Oncofertility Unit. A total of 96 patients were referred to the Oncofertility Unit for evaluation after the diagnosis of cancer and before gonadotoxic treatment between April 2011 and June 2014. Of the 96 patients, 30 (31.2%) were affected by breast cancers, 20 (20.8%) by sarcomas, 28 (29.2%) by hematologic malignancies, 13 (13.5%) by central nervous system cancers, 3 (3.1%) by bowel tumors, 1 (1.0%) by Wilms' tumor, and 1 (1.0%) by a thyroid tumor; 47 (49.0%) were referred for oocyte cryopreservation before starting chemotherapy, 20 (20.8%) were referred for ovarian tissue cryopreservation, and 29 (30.2%) were not recruited. The mean time between the patients' counseling and oocyte retrieval was 15 days (range, 2–37 days). The mean time between the laparoscopic surgery and the beginning of treatment was 4 days (range, 2–10 days). The number of patients who were referred increased over time, whereas the rate of patients who were not recruited decreased, showing an improvement in referrals to the Oncofertility Unit and in the patients' counseling and understanding. Our results indicate that an effective multidisciplinary oncofertility team is necessary for prompt referrals and treatment.